Prolaps Tali Pusat pada Skor Zatuchni-Andros Baik : Sebuah Laporan Kasus Tantangan Persalinan Sungsang - I Gede Agus Rio Saputra; I Made Pasek Soma Gauthama (Pusat Riset dan Inovasi Nasional, 2024)
Breech delivery remains an obstetric challenge due to its potential for intrapartum and neonatal complications. One rare yet potentially fatal complication is umbilical cord prolapse, particularly in footling presentations. This case report was developed based on clinical observation and medical documentation of a 29-year-old woman, gravida 2 para 1, at 39–40 weeks of gestation, who experienced cord prolapse during breech labor despite having a Zatuchni–Andros score of 5, indicating a favorable prognosis for vaginal delivery. The patient was planned for a vaginal delivery under close monitoring; however, during the active phase of the first stage of labor, spontaneous rupture of membranes occurred, immediately followed by umbilical cord prolapse with irregular fetal heart rate (82–90 beats per minute). Emergency management included manual cord reposition, Trendelenburg positioning, oxygen administration, and an urgent cesarean section. The male infant, weighing 2,995 grams, was delivered with no spontaneous cry and an Apgar score of 0–0, indicating severe asphyxia, while the mother remained stable postoperatively. This case highlights that although a favorable Zatuchni–Andros score suggests good prognosis, dynamic intrapartum factors such as membrane rupture and fetal position may precipitate sudden cord prolapse. The neonatal outcome is highly dependent on the decision-to-delivery interval, ideally within 30 minutes. Continuous fetal monitoring, intensive intrapartum supervision, and readiness for emergency cesarean section are essential to prevent perinatal morbidity and mortality.